A GIS-Investigation of Four Early Anglo-Saxon Cemeteries: Ripley's K-function Analysis of Spatial Groupings Amongst Graves. (February 2013) - Sayer, Duncan; Wienhold, Michelle
Archaeologists have often used their "eye" to interpret spatial patterns within cemetery sites. In this article, we will use Ripley's K -function analysis to determine the proximity of statistically significant clusters within four early Anglo-Saxon cemetery sites: Wakerley, Norton, Berinsfield, and Lechlade. Using spatial and statistical methods supported by ArcGIS 10 we will explore the kernel density estimates of graves at the point of significance to discuss the organization of cemeteries as part of their chronological and social development. As a result of this investigation we will conclude that these sites were not organized into small clusters of nuclear family graves but large plots that contained the remains of varied, multivocational households.